Plasmacytic or lymphoplasmacytic infiltrate in lymph nodes: Diagnostic approach and differential considerations - Yi Xie; Bethany Vallangeon; Xin Liu; Anand S Lagoo (Wolters Kluwer Medknow Publications, 2016)
Plasmacytosis is a common finding in lymph node biopsies and can be seen in diverse circumstances ranging from reactive lymphadenopathy to malignant lymphoma. Familiarity with various histopathologic features of the different entities and awareness of their typical clinical and ancillary study findings are essential for an accurate diagnosis. In this review, we present common and representative nonneoplastic entities and lymphomas that have plasmacytic differentiation or associated plasmacytosis. We focus on the histological classification with an emphasis on the diagnostic approach and areas of diagnostic challenge.